(untitled) (Nonconventional Technologies Review, 2022)
A porous high-strength material having load-bearing thermal insulation properties suitable as light filling material for building foundation, drainage, road construction, underground insulation of heat pipes, etc. was experimentally made by sintering and foaming at 830-840 ºC applying the microwave irradiation to a pressed powder mixture composed of recycled post-consumer glass, glycerol, calcium carbonate, water glass and water. The manufacturing recipe adopted by authors is original by combining a liquid carbonaceous expanding agent (glycerol) with a solid agent (calcium carbonate) aiming at the increase of compressive strength at 6.5-7.6 MPa, the product bulk density being under 0.20 g cm-3. The nonconventional technique of predominantly direct microwave heating is also original and more economical compared to conventional methods applied both in industrial processes and in small-scale experiments.